PERKAWINAN DI BAWAH UMUR DALAM HUKUM ADAT BALI DITINJAU DARI UU NO. 1 TAHUN 1974 TENTANG PERKAWINAN DAN UU NO. 35 TAHUN 2014 TENTANG PERLINDUNGANANAK - Loresta Cahyaning Lintang; Rama Pramu Wicaksono (Journal of Law, Society, and Islamic Civilization, 2015)
Purpose of Marriage Act is to create a society that is the rule of law and legal certainty for the people who are bound by marriage with the diversity of culture and the existence of customary law are still inherent in the culture in Indonesia. Where problems in the Marriage Act contained in the validity of underage marriage in Article 7 paragraph (1) and paragraph (2) of the Act 1 of 1974 that "(1) Marriage is only allowed when the man reaches the age of 19 (nine twelve) years and the woman has reached the age of 16 (sixteen) years, (2) In the case of irregularities in paragraph (1) of this section may request a dispensation to court or other official requested by both parents the man or the woman ". This condition is deviated by Act No. 23 of 2002 on Child Protection in Article 26 paragraph (1) letter c, which states that "Parents have the duty and responsibility to prevent marriage at the age of children". Revision of the Marriage Act is very necessary, especially regarding the dispensation of the court and marry the age limit given the confusion between the Marriage Act with Child ProtectionAct.